Metabolic milieu associates with impaired skeletal characteristics in obesity. - Heli T Viljakainen; Heikki A Koistinen; Taina Tervahartiala; Timo Sorsa; Sture Andersson; Outi Mäkitie (PLoS ONE, 2017)
High leptin concentration, low-grade inflammation, and insulin resistance often coexist in obese subjects; this adverse metabolic milieu may be the main culprit for increased fracture risk and impaired bone quality seen in patients with type 2 diabetes. We examined the associations of leptin, hs (high sensitivity)- CRP and insulin resistance with bone turnover markers (BTMs) and bone characteristics in 55 young obese adults (median BMI 40 kg/m2) and 65 non-obese controls. Mean age of the subjects was 19.5 ± 2.5 years (mean ± SD). Concentrations of leptin, adiponectin, hs-CRP, MMP-8 and TIMP-1, fasting plasma glucose and insulin (to calculate HOMA), BTMs (BAP, P1NP, CTX-1, and TRAC5b) were measured. Bone characteristics were determined with pQCT at radius and tibia, and with DXA for central sites. Leptin, hs-CRP and HOMA correlated inversely with BTMs: the partial coefficients were 1.5-1.9 fold higher in males than in females. After adjusting for age, BMI, and other endocrine factors, leptin displayed an independent effect in males on radial bone mass (p = 0.019), tibial trabecular density (p = 0.025) and total hip BMD (p = 0.043), with lower densities in males with high leptin. In females, the model adjusting for age, BMI, and other endocrine factors, revealed that hs-CRP had independent effects on radial bone mass (p = 0.034) and lumbar spine BMD (p = 0.016), women with high hs-CRP having lower values. Partial correlations of adiponectin and TIMP-1 with bone characteristics were discrepant; MMP-8 showed no associations. In conclusion, in young obese adults and their controls, leptin, hs-CRP and HOMA associate inversely with BTMs and bone characteristics. Leptin appears to be the key independent effector in males, whereas hs-CRP displayed a predominant role in females.